Numerical validation of the fire performance of fire fighter clothing and experimental tests - Pereira, Vitor (2020)
The Fire Protection Clothe (FPC) of firefighters have been investigated over the last years in several terms to improve the safety of their users. FPC are designed to save the firefighters from excessive heat and fire conditions, allowing for a period of time, usually required for a rescue mission, fighting fire, or withdrawing from direct flame contact. The FPC fabrics are design in order to settle a certain degree of comfort to firefighters when exposed to accidental conditions. The heat source, intensity of fire, time of exposure, and other variables affect the protection of the FPC. The FPC is a multilayer assembly composed of various types of woven and nonwoven fabrics. Conventional fibres such as cotton, wool, and viscose and highperformance fibres such as aramid, polybenzimidazole, and polybenzoxazole (PBO) are used in FPC [1].